Karakterisasi Keluhan Muskuloskeletal Akibat Postur Kerja Buruk Pada Pekerja Industri Kecil Makanan - Luciana Triani Dewi (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2016)
The study was originated from the result of observation on production activity of small food industries in Yogyakarta that showed various awkward postures. Awkward posture will lead to continual static loading on soft tissue which potentially cause musculoskeletal disorders and further will affect worker productivity and performance. The aims of the study were to identify and characterize musculoskeletal symptoms among small food industry worker in Yogyakarta. The subjects of this study were one hundred worker of small food industry in Yogyakarta. The identification used standardized Nordic Questionnaire to evaluate musculoskeletal symptoms on 28 body parts in two time periods: recent twelve months and recent seven days. The result of this study indicated that 100% participants reported experiencing discomfort at least in one body part in the previous twelve months and 89% of them reported the same thing in the seven-day period. Statistical analysis showed significant difference between musculoskeletal symptoms taking place in the twelve-month period and those in the seven-day period. Musculoskeletal symptoms primarily took place on waist. The lowest prevalence for twelve-month period and seven-day one were left elbow (29%) and left leg (5%), respectively.